THE INFLUENCE OF MOTIVATION AND INTERPERSONAL COMMUNICATION ON MEMBER COMMITMENT AT YRB - Rinta Uli Artha; Uce Suganda (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the influence of motivation and interpersonal communication on member commitment in the nonprofit organization YRB. The research background is based on the decline in organizational membership during the 2021–2025 period and the low level of active member participation in organizational activities.This research employs a quantitative approach. The population consists of all active members of YRB, with motivation and interpersonal communication as independent variables, with organizational commitment as the dependent variable. Data were collected through questionnaires, while statistical analysis techniques were used to examine the relationships among variables. The results indicate that motivation has a significant effect on member commitment. In addition, interpersonal communication was found to influence both the increase and decrease of organizational commitment. Effective interpersonal communication strengthens members’ commitment within the organization. These findings suggest that enhancing member commitment in YRB can be achieved by strengthening intrinsic and extrinsic motivation as well as improving interpersonal communication. This study is expected to provide theoretical contributions to human resource management and organizational behavior literature, and to serve as a practical reference for nonprofit organizations seeking to enhance member commitment.